The Unintended Consequences of Education Policies on South African Participation and Unemployment - Rulof Burger; Servaas van der Berg; Dieter von Fintel (Institute for the Study of Labor (IZA), 2013)
In the late 1990s the South African Department of Education implemented two policies that were meant to reduce the large number of over-age learners in the school system: schools were no longer allowed to accept students who were more than two years older than the correct grade-age and students could not be held back more than once in each of four schooling phases. Our analysis uses school administrative data and household survey data to show that these policies coincided with a decrease in school enrolment of at least 400,000 and possibly more than 900,000 learners. These policies appear to have pushed many students into the labour market at earlier ages than was observed for previous generations, which explains much of the sudden increase in labour force participation and unemployment during this period. However, since these individuals would probably have entered the labour market sooner if not for their poor employment prospects, we argue that the resulting increase in unemployment signifies a more accurate reflection of disguised unemployment that already existed in the mid-1990s rather than a deterioration of labour market conditions.
Keywords: J21; I25; J64; 330; South Africa; education; unemployment; participation